Steady State Gate Operation Model for Mun Bon Irrigation System - Vudhivanich, Varawoot; Roongsri, Supachai (Agriculture and Natural Resources, 2001)
The steady state gate operation model was formulated in this study to help irrigation engineers operating the complicated irrigation canal regulators. The computer program called GATEOP was developed for calculating the water surface profile of the canal reach and the gate opening. The model was applied to Mun Bon irrigation project. Six main regulators which are the entrance to 6 zones in water master 2 were selected for the model testing. The field data of the regulators and the canal sections such as gate length, gate sill elevation, canal bed elevation downstream of the regulator, full supply level, maximum design discharge, canal bed slope, bed width and side slope were investigated. The 6 regulators were calibrated intensively. The field test during June-November 1998 shown that the discharge control of the 6 regulators were less than ± 10% error.